Behavior analysis for lasting change - Beth Sulzer-Azaroff (Holt, Rinehart, and Winston, 1991)
Introduces the concepts and methods of applied behavior analysis based on solid theory and research. Provides strategies for developing and implementing solutions to problem situations. Emphasizes a systems approach as a means of initiating more effective and durable change